DETEKSI MATA REAL TIME MENGGUNAKAN OPENCV UNTUK ANDROID - Erliani, Yustika; Priambodo, Bagus (PETIR, 2015)
Right now there has been a lot of developing applications that use the face detection feature. Face detection itself can be done in various ways, one using the Viola-Jones method, a method that combines support vector machines, boosting algorithm, and a cascade classifie. In this research designed an eye detection system by using a Viola-Jones method with OpenCV library. Data from this research are in the form of a live video capture using camera smartphone with android os